The Transformational Use of Information and Communication Technologies in Africa - Yonazi, Enock; Kelly, Tim; Halewood, Naomi; Blackman, Colin (World Bank, Washington, DC, and African Development Bank, Tunis, 2017)
This new flagship report for the eTransform Africa Project, produced by the World Bank and the African Development Bank, with the support of the African Union, identifies best practice in the use of Information and communication technologies (ICTs) in key sectors of the African economy. Under the theme transformation-ready, the growing contribution of ICTs to agriculture, climate change adaptation, education, financial services, government services, and health is explored. In addition, the report highlights the role of ICTs in enhancing African regional trade and integration as well as the need to build a competitive ICT industry to boost innovation, job creation, and the export potential of African companies.